Parents and Health Care Providers' Perspectives on Vital Signs Monitoring Technologies in the Neonatal Intensive Care Unit: An International Survey - Senechal, Eva; Radeschi, Daniel; Kearney, Robert; Shalish, Wissam; Sant'Anna, Guilherme (American Journal of Perinatology, 2025)
This study aimed to assess the views of parents and neonatal intensive care unit (NICU) health care providers (HCPs) on current wired vital signs monitoring and future wireless alternatives.Prospective cross-sectional survey was conducted between March and July 2023, targeting three groups: (1) NICU parents, (2) physicians, and (3) nurses and respiratory therapists (RT) and physiotherapists (PT). A 17-question survey was developed to assess several perspectives with current vital signs monitoring and a possible wireless monitoring system. NICU parents completed paper surveys and HCPs participated via an anonymous electronic survey. The original English survey was tailored for different respondent groups, translated into French, Spanish, and Portuguese, and distributed through neonatal research networks. Responses from each group were analyzed as totals (%), with within-group comparisons assessed using the Wilcoxon signed-rank test. Additionally, between-group comparisons were conducted using the chi-square test of independence or Fisher's exact test, as appropriate.A total of 1,141 responses were included (25 parents, 438 physicians, and 678 nurses, RTs, and PTs). Only 52% of parents were satisfied with current wired systems; 68% reported wires hindered infant handling, and 52% cited interference with skin-to-skin care. Both physicians and HCPs expressed low satisfaction with the current system. Common concerns included tangling, skin irritation, and workload. Support for wireless technology introduction was high across all groups (parents = 60%, physicians = 91%, and nurses, RTs, and PTs = 87%), with main perceived benefits including improved kangaroo mother care (KMC), reduced patient discomfort, and enhanced bonding. All groups expressed accuracy, safety, battery life, and cost concerns of a possible wireless system.Parents and HCPs are generally dissatisfied with the current NICU vital signs monitoring systems, primarily due to concerns with wires and cables and interference with KMC. Wireless technologies were mostly supported, but data on reliability, safety, and economic feasibility will be critical for development and successful implementation.
Keywords: patient monitoring; wireless technology; survey; parents; health care providers